Tokopedia E-Commerce Retail Business Innovation in the Transformation Retail Industrial Era 4.0 - Asiyah, Siti (Universitas Bina Sarana Informatika, 2023)
Tokopedia's strategy in the world of retail 4.0 will be explained in this paper. The transformation of the retail world occurred from the 1.0 era to the 4.0 era and each has its characteristics. Tokopedia was born when it was in the retail 3.0 era and began to grow in the 4.0 era. A business model innovation strategy is very necessary for the business to survive in the online marketplace. Many innovations have been carried out, including (1) store management facilities (2) Shopping by type category of goods sold and business processes are very easy to learn (3) For easy access to online shops, sellers receive their accounts created during initial registration (4) Collaboration with various transportation services facilitates delivery of goods to consumers (5) simple payments and safe. The method used is to collect some literature to further identify whether it is by the topic to be discussed and make important points related to Tokopedia's strategy in the 4.0 era.